Leg length preservation with pedicled fillet of foot flaps after traumatic amputations. - Ghali, S; Harris, P; Khan, U; Pearse, M; Nanchahal, J (2005)
Six patients with insufficient soft-tissue coverage after lower limb trauma were treated with pedicled fillet of foot flaps to achieve primary stump closure and to preserve leg length. The flaps used were all based on either the posterior tibial neurovascular pedicle, the anterior tibial neurovascular pedicle, or both. Five flaps survived; one patient required conversion of a through-knee to an above-knee amputation and debridement of the flap because of venous thrombosis of the pedicle. In three of the cases, a functional knee joint was preserved. The patients ranged in age from 21 to 54 years, the mean hospital stay was 55.5 days (range, 28 to 76 days), and the mean follow-up time was 14.5 months. Despite an average of 4.3 procedures from initial admission to first discharge and an average of 2.0 postamputation procedures to achieve primary stump healing, all patients have achieved independent mobility with their prosthesis. The advantages of preserving leg length and, where possible, preserving a functional knee joint compensate for repeated procedures on these patients. When planned well, a pedicled fillet of foot flap therefore achieves the aims of amputation, namely, providing primary healing of a sensate, durable, cylindrical stump that is pain-free and preserves maximal leg length. This is achieved with no donor-site morbidity and with no need for microvascular reconstruction.